Robot-assisted hysterectomy for endometrial and cervical cancers: a systematic review. Issue 1 (March 2017) - Nevis, Immaculate; Vali, Bahareh; Higgins, Caroline; Dhalla, Irfan; Urbach, David; Bernardini, Marcus
Abstract Total and radical hysterectomies are the most common treatment strategies for early-stage endometrial and cervical cancers, respectively. Surgical modalities include open surgery, laparoscopy, and more recently, minimally invasive robot-assisted surgery. We searched several electronic databases for randomized controlled trials and observational studies with a comparison group, published between 2009 and 2014. Our outcomes of interest included both perioperative and morbidity outcomes. We included 35 observational studies in this review. We did not find any randomized controlled trials. The quality of evidence for all reported outcomes was very low. For women with endometrial cancer, we found that there was a reduction in estimated blood loss between the robot-assisted surgery compared to both laparoscopy and open surgery. There was a reduction in length of hospital stay between robot-assisted surgery and open surgery but not laparoscopy. There was no difference in total lymph node removal between the three modalities. There was no difference in the rate of overall complications between the robot-assisted technique and laparoscopy. For women with cervical cancer, there were no differences in estimated blood loss or removal of lymph nodes between robot-assisted and laparoscopic procedure. Compared to laparotomy, robot-assisted hysterectomy for cervical cancer showed an overall reduction in estimated blood loss. Although robot-assisted hysterectomy is clinically effective for the treatment of both endometrial and cervical cancers, methodologically rigorous studies are lacking to draw definitive conclusions.